P018 Local entrainment and distribution across cerebral networks of natural oscillations elicited in implanted epilepsy patients by intracranial stimulation: Paving the way to develop causal connectomics of the healthy human brain. Issue 3 (March 2017) - Amengual, J.; Moreau, T.; Stengel, C.; Adam, C.; Valero-Cabré, A.
Abstract : Introduction: The frequency of local oscillations and inter-regional synchrony has been correlated with the engagement of cognitive operations. Notwithstanding, adding causality to these associations requires the direct manipulation of brain rhythms Noninvasive stimulation with single pulses of TMS coupled to scalp-EEG recordings has provided evidence of local increases in power at specific frequency bands, likely to reflecting the local "natural" frequencies as defined by Rosanova et al. (2009). Mapping of these phenomena across human brain areas is paramount for understanding the neural coding mechanisms involved in information transfer and to further develop the use of exploratory and therapeutic neuromodulation. Objectives: Mapping the human anatomical and physiological causal features of spreading natural oscillations across brain regions by co-localizing an atlas of structural connectivity with a map of functional interactions based on the distribution of rhythmic activity enabled by intracortical stimulation. Methods: We analyzed intracranial EEG signals from 8 epilepsy patients implanted with depth multielectrodes in frontal, prefrontal, parietal and temporal areas, the amygdala and the hippocampus. We analyzed in the frequency-domain oscillatory activity elicited by single electrical pulses delivered through pairs of adjacent contacts, as recorded by the remaining contacts, and modeled a map of effective connectivity. Individual anatomical maps of white matter fasciculi were tracked individually and co-localized with the former. Results: Single electrical pulses induced frequency-specific modulations of power in contacts not employed to deliver the pulses. Oscillatory enhancements were influenced by both the local anatomical environment and the estimated probability of white matter connections between stimulated and recorded sites. Conclusions: Our results support the feasibility of studying functional connectivity patterns by analyzing the local induction and network spread of natural oscillation frequencies, enabled by single pulses of intracranial stimulation and to co-register them with white matter connectivity maps. This approach might contribute to the compilation whole-brain connectivity atlases able to categorize oscillation frequency to behavioral relationships throughout brain regions and their connections in humans.